David F. Garcia. 2017. Listening for Africa: Freedom, Modernity, and the Logic of Black Music’s African Origins. - Buchea, Jason (Journal of World Popular Music, 2021)
David F. Garcia. 2017. Listening for Africa: Freedom, Modernity, and the Logic of Black Music’s African Origins. Durham, NC: Duke University Press. xii + 360 pp. ISBN 9780822363705 (pbk)